Troubleshooting injection moulding : an Arburg guide - Goodship, Vannessa (Rapra review reports ;, 2004)
This review is based on years of experience in injection moulding. Dr Goodship is an expert moulder and Arburg is a well known manufacturer of injection moulding machines. The review is packed with useful diagrams and flow charts to identify problems and help to find solutions. There are many papers published on this subject and an extensive, indexed set of abstracts compiled from the Polymer Library accompanies the review.